(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Women are going ahead in all the fields from kitchen to space. They are establishing their mark wherever they go and are paving way for many others to join. But still many women are not able to enter into the field of research. Women are encountering many problems during their journey to become a researcher from all dimensions. Thus this study focused on identifying the issues and challenges of women during their research activities and observed that lack of financial resources and lack of facilities are the main problems hindering their growth.